2014
DOI: 10.1111/pim.12148
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized gene expression of toll‐like receptors 2, 4 and 9 in the brain and peripheral lymphoid organs during canine visceral leishmaniasis

Abstract: Visceral leishmaniasis is an important parasitic disease that affects humans and animals. The response against the protozoan involves the interaction of both innate and adaptive branches of the immune system, and an important immune sensor is represented by the toll-like receptor (TLR) family. Here, we investigated the pattern of TLR-2, TLR-4 and TLR-9 gene expression in different compartments (brain, choroid plexus, spleen and lymph node) of dogs naturally infected with Leishmania infantum. Gene expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
4
19
2
Order By: Relevance
“…been previously found in several tissues, including skin, 28,29 blood, 30 liver, 29 brain, spleen and lymph node. 31 Here, in addition to a higher relative expression of TLR-2 in affected dogs, we observed a significant difference in transcript abundance between dogs with low-to- Although TLR-2 is deemed to alter production of NO, 17,18 our data did not support a correlation with changes in expression of iNOS, in agreement with observations made in TLR-2-deficient mice. 22 Of note, TNFα has also been previously suggested to modulate induction of iNOS, 20,33-35 while IL-10 was reported to have inhibitory effects on the production of the enzyme.…”
Section: Increased Expression Of Tlr-2 During Canine Leishmaniosis Hassupporting
confidence: 80%
See 1 more Smart Citation
“…been previously found in several tissues, including skin, 28,29 blood, 30 liver, 29 brain, spleen and lymph node. 31 Here, in addition to a higher relative expression of TLR-2 in affected dogs, we observed a significant difference in transcript abundance between dogs with low-to- Although TLR-2 is deemed to alter production of NO, 17,18 our data did not support a correlation with changes in expression of iNOS, in agreement with observations made in TLR-2-deficient mice. 22 Of note, TNFα has also been previously suggested to modulate induction of iNOS, 20,33-35 while IL-10 was reported to have inhibitory effects on the production of the enzyme.…”
Section: Increased Expression Of Tlr-2 During Canine Leishmaniosis Hassupporting
confidence: 80%
“…Increased expression of TLR‐2 during canine leishmaniosis has been previously found in several tissues, including skin, blood, liver, brain, spleen and lymph node . Here, in addition to a higher relative expression of TLR‐2 in affected dogs, we observed a significant difference in transcript abundance between dogs with low‐to‐moderate and moderate‐to‐high parasite load.…”
Section: Discussionsupporting
confidence: 67%
“…This has been extensively studied in both human and murine models (Kropf et al 2004 a ; Liese et al 2007; Raman et al 2010; Tuon et al 2010; Gallego et al 2011). However, there is a limited amount of information about the role that these receptors play in canine L. infantum infection (Figueiredo et al 2013, 2014; Melo et al 2014 a ). To date, 10 TLRs have been characterized in humans with 12 found to be functional in mice (Kawai and Akira, 2011) and 10 in dogs (Cusco et al 2014).…”
Section: Tlrsmentioning
confidence: 99%
“…This increased transcription could have been due to an influx of inflammatory cells into the spleen, in particular at the beginning of the infection, and a decrease seen at the chronic stage of infection could possibly have been due to partial control of the infection (Cezario et al 2011). In a recent study looking at naturally infected dogs, Melo et al reported increased TLR2 and TLR4 expression in the spleens of naturally infected dogs compared with non-infected dogs (Melo et al 2014 a ). This elevated expression could indicate that these TLRs are important for the control of the infection and they are elevated in an attempt to eliminate the parasite.…”
Section: Tlrsmentioning
confidence: 99%
“…It should be noted that these symptoms are very generic, and then, it is quite difficult to link these neurological abnormalities with Leishmania infection. Indeed, post‐mortem studies have revealed that signs of brain alterations are frequently found in dogs that did not present any sign of neurological disease . To this, the choroid plexus is considered one important route for the entrance of inflammatory mediators, cells and parasites into the CNS .…”
Section: Clinical Features and Neurological Alterations In Canine Leimentioning
confidence: 99%